2018
DOI: 10.1111/php.13053
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Functionalized Fullerenes and Surface‐Modified TiO2 Nanoparticles to Photosensitize Peroxidation of Lipids in Selected Model Systems

Abstract: Photochemical properties of a new class of inorganic nanoparticles, namely a cationic C60 fullerene substituted with three quaternary pyrrolidinium groups (BB6) and a surface‐modified nanocrystalline TiO2 with bromopyrogallol red (Brp@TiO2) were examined for their effectiveness in photogenerating singlet oxygen and free radicals. In particular, their ability to photosensitize peroxidation of unsaturated lipids was analyzed in POPC:cholesterol liposomes and B16 mouse melanoma cells employing a range of spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Inorganic nanoparticles, including silica nanoparticles, gold nanoparticles, copper nanoparticles, and nanotubes, have good biocompatibility and enable simultaneous imaging and drug delivery ( 47 , 48 ). However, these nanoparticles may not permit specific targeting to the affected region and generally need to be coupled with other targeting ligands.…”
Section: Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic nanoparticles, including silica nanoparticles, gold nanoparticles, copper nanoparticles, and nanotubes, have good biocompatibility and enable simultaneous imaging and drug delivery ( 47 , 48 ). However, these nanoparticles may not permit specific targeting to the affected region and generally need to be coupled with other targeting ligands.…”
Section: Nanotechnologymentioning
confidence: 99%
“…Kozinska et al. applied functionalized fullerenes and surface-modified TiO 2 as a photosensitizer for melanoma treatment and demonstrated that novel inorganic nanoparticles can achieve photodynamic killing of melanoma cells; this novel inorganic TiO 2 nanoparticle complex was shown to have a longer retention time in vivo and to be nontoxic and stable under conditions without light irradiation ( 47 ). Ferreira et al.…”
Section: Nanotechnologymentioning
confidence: 99%
“…In the presence of light and hydrogen peroxide, redox-active metal ions such as iron and copper can generate hydroxyl radicals and possibly other reactive oxygen species (ROS) [ 6 ]. Moreover, certain semiconductors such as titanium dioxide (TiO 2 ) and zinc oxide (ZnO) irradiated with visible or near-UV light can produce oxygen radicals and singlet oxygen [ 6 , 7 , 8 ]. Organic compounds including dyes, porphyrins, and aromatic hydrocarbons (e.g., benzo[a]pyrene) present in airborne pollution [ 9 , 10 , 11 , 12 , 13 ] can exhibit substantial photosensitizing ability to generate singlet oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials possess their unique physical and chemical properties as a result of quantum effect, largely influenced by the size and geometry of the material [26,27]. Another beneficial aspect of nanoscale surface topography of the materials is high surface area and its interactions with biologically important molecules present in bacteria cells (e.g., proteins, DNA, or lipid membranes) [28][29][30]. Nano-sized agents are able to enhance the internalization processes, locally change the microenvironment near the bacteria, increase solubility, and generate ROS responsible for bacterial cells damage [31,32].…”
Section: Introductionmentioning
confidence: 99%